Augmented Reality in Ethnomathematics: Developing an Interactive Magazine to Enhance Students' Spatial Skills in Cube and Cuboid Geometry - Fatma , Nazira; Kamid; Anwar, Khairul (Science and Mathematics Education Journal, 2025)
Augmented Reality (AR) has revolutionized mathematics education by providing interactive and immersive learning experiences. However, its integration into ethnomathematics-based learning remains underexplored, particularly in geometry instruction. This study aims to develop an Interactive Augmented Reality Magazine to enhance students' spatial skills in understanding cube and cuboid geometry through an ethnomathematical approach. The research employs the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional model to systematically design and develop the AR-based learning material. The study was conducted at SMP Negeri 11 Kota Jambi, involving students in a classroom setting. The research stages include: (1) analyzing ethnomathematical concepts related to cube and cuboid in local cultural artifacts, (2) designing an AR-integrated interactive magazine, (3) developing the learning media, (4) implementing the materials in real classroom settings, and (5) evaluating students' spatial skills improvement using pre-test and post-test assessments. The findings reveal that the integration of AR in ethnomathematics-based learning significantly enhances students' spatial visualization and engagement. Students showed increased ability to manipulate 3D geometric objects, understand mathematical structures within cultural contexts, and apply spatial reasoning more effectively. Additionally, their motivation and interest in learning geometry improved. This study underscores the potential of AR-enhanced learning in making abstract mathematical concepts more tangible and culturally relevant. It is recommended that future research explore AR applications in other mathematical topics and conduct longitudinal studies to assess long-term effects on students' cognitive and problem-solving skills.